2001
DOI: 10.1021/la001307e
|View full text |Cite
|
Sign up to set email alerts
|

Colloid Polymer Interactions and Aggregation in Aqueous Mixtures of Polystyrene Latex, Sodium Dodecyl Sulfate, and a Hydrophobically Modified Polymer:  A Dynamic Light Scattering Study

Abstract: The kinetics of clusters formed in the flocculation process of polystyrene latex particles (PSL) in the presence of hydrophobically modified ethyl(hydroxyethyl)cellulose (HM-EHEC) and sodium dodecyl sulfate (SDS) in the concentration interval of 2-4 mmolal have been investigated with the aid of dynamic light scattering measurements at different temperatures. For this system (HM-EHEC/SDS/PSL) we observe an intriguing time-dependent cluster growth over a restricted (2-4 mmolal) surfactant concentration range. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In this study, a nonexponential behavior of the autocorrelation function was observed, and in accordance with previous DLS studies on colloidal particles [33][34][35][36] a stretched exponential function was employed in the analysis of correlation function data to allow deviations from a single exponential behavior…”
Section: Dynamic Light Scatteringsupporting
confidence: 80%
“…In this study, a nonexponential behavior of the autocorrelation function was observed, and in accordance with previous DLS studies on colloidal particles [33][34][35][36] a stretched exponential function was employed in the analysis of correlation function data to allow deviations from a single exponential behavior…”
Section: Dynamic Light Scatteringsupporting
confidence: 80%
“…A conspicuous feature is the high amount of adsorbed HM-HEC, on both surfaces, in comparison with that of HEC. Previous adsorption studies [20][21][22] of aqueous solutions of EHEC and HM-EHEC have revealed that the more hydrophobic counterpart has usually a higher affinity to adsorb onto different substrates. An interesting feature is the fact that a higher surface coverage is observed for gold surfaces with citrate-layer, and this effect is more pronounced for HEC than HM-HEC (see Fig.…”
Section: Adsorption Of Hec and Hm-hecmentioning
confidence: 99%
“…Hydroxyethylcellulose (HEC), on the other hand, is essentially a hydrophilic polymer and this cellulose derivative displays rather weak thermoresponsive properties. It has been established in previous papers that a large amount of EHEC is adsorbed onto polystyrene latex particles [20][21][22]. If we take into account that the EHEC polymer contains hydrophobic microdomains in addition to regions of hydrophilic nature, one would expect the adsorption behavior to be altered when surfaces of different hydrophobicity are employed and the polymer is exposed to further hydrophobic modification.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all suspensions having particle size less than 1 mm are inherently thermodynamically unstable due to the natural tendency decrease the large specific surface area and excess surface energy (Patel, 2010). For this purpose, wetting/dispersing agents are used to stabilize the suspension against flocculation (Holthoff et al, 1996;Lauten et al, 2001) and crystal growth (Ostwald ripening (Ostwald, 1901)). …”
Section: Introductionmentioning
confidence: 99%